That Was Easy! Expectancy Violations During Exposure and Response Prevention for Childhood Obsessive-Compulsive Disorder. Issue 3 (May 2020) - Guzick, Andrew G.; Reid, Adam M.; Balkhi, Amanda M.; Geffken, Gary R.; McNamara, Joseph P. H.
Violating expectancies during exposure therapy is proposed to promote inhibitory learning and improved treatment outcomes. Because people tend to overestimate how distressing emotionally challenging situations will be, violating expectations of distress may be an intuitive way to promote treatment outcome during exposure-based cognitive-behavioral therapy (CBT). This study evaluated overpredictions of distress during exposure tasks in 33 youth with obsessive-compulsive disorder (OCD; ages 8-17) participating in CBT. Youth with more variable prediction accuracy and a higher proportion of overpredictions experienced more rapid symptom reduction, b = −0.29, p = .002. Underpredictions were less common toward the end of therapy as youth experienced less severe OCD, b = 0.12, p= .001. Findings suggest that although youth often accurately predict the intensity of exposure, overpredictions are common as well. The frequency of these overpredictions promoted treatment outcome, supporting expectancy violations as one indicator of inhibitory learning during exposure therapy.